The Influence of Brand Ambassador and Digital Payment on Purchase Decision Through Impulsive Buying Mediation on Scarlett Whitening - Nusantara, Aiza Duta Dwipa; Fadhilah, Muinah; Setiawan, Budi (Economics and Business Solutions Journal, 2025)
This study aims to examine the influence of Brand Ambassadors and Digital Payment on Purchase Decisions, with Impulsive Buying acting as a mediating variable in the context of Scarlett Whitening products. A quantitative research method was employed, utilizing a survey approach through questionnaires distributed to 157 respondents who had previously purchased Scarlett Whitening products. The results indicate that both Brand Ambassadors and Digital Payment have a positive and significant impact on Purchase Decisions, both directly and indirectly through the mediation of Impulsive Buying. The findings suggest that consumers tend to make quicker and less deliberative purchase decisions when influenced by appealing Brand Ambassadors and the convenience of Digital Payment options. Furthermore, this study highlights the crucial role of Impulsive Buying as a behavioral factor that strengthens the relationship between marketing strategies and consumer purchasing behavior. The implications of this research provide valuable insights for businesses, particularly in the beauty and skincare industry, on how to optimize their marketing strategies. Companies can enhance their brand appeal and drive higher purchase rates by strategically leveraging Brand Ambassadors and offering seamless Digital Payment methods. Ultimately, this study contributes to the growing body of knowledge on consumer behavior and digital marketing strategies in the modern retail landscape